The antifibrotic effect of pheretima protein is mediated by the TGF-β1/Smad2/3 pathway and attenuates inflammation in bleomycin-induced idiopathic pulmonary fibrosis. (25th March 2022) - Li, Shuyu; Yang, Qixin; Chen, Feilong; Tian, Linhua; Huo, Jinhai; Meng, Yanli; Tang, Qingfa; Wang, Weiming
Abstract: Ethnopharmacological relevance: Pheretima is a traditional Chinese medicine that could treat various lung diseases such as asthma, pneumonia, and lung cancer effectively; however, limited studies on the use of Pheretima protein in the treatment of lung diseases have been conducted to date. Aim of the study: The aim of this study was to explain the antipulmonary fibrosis mechanism of the Pheretima protein and elucidate its possible cell signaling pathways. Material and methods: Fresh pheretima was freeze-dried to obtain the Pheretima protein. Divide C57BL/6 mice into control and bleomycin (BLM)-induced models, pirfenidone, and Pheretima protein-treatment groups. Three weeks later, they were treated with H&E and Masson's trichrome staining to assess lung injury and fibrosis. Pulmonary fibrosis was assessed using immunohistochemistry (IHC), realtime-PCR (RT-PCR), and western blotting. Inflammation was assessed using the alveolar lavage fluid. Results: Pheretima protein inhibited epithelial-mesenchymal transition (EMT) and extracellular matrix (ECM) deposition and reduced inflammation. It also reduced the levels of Smad2/3, pSmad2/3, and transforming growth factor-beta 1 (TGF-β1). Thus, our results indicate that Pheretima protein can alleviate BLM-induced pulmonary fibrosis in a mouse model. Conclusion: Pheretima protein inhibits ECM, EMT, and antiinflammatory markers, which in turn ameliorates BLM-induced pulmonary fibrosis. Preliminary mechanistic studies indicated that Pheretima protein can exert its biological activity by downregulating the TGF-β1/Smad2/3 pathway. Graphical abstract: Image 1 Highlights: Treatment with Pheretima Protein recovered lung function in the BLM-induced mouse. Pheretima Protein attenuates pulmonary fibrosis by inhibiting TGF-β1/Smad2/3. This study found that Pheretima Protein therapy might be a potential therapeutic agent for treatment of pulmonary fibrosis.